Negative electrode and secondary battery including the same
By introducing a carbon material structure containing sheet-like artificial graphite and natural graphite into the negative electrode active material of the secondary battery, the problem of low negative electrode adhesion is solved, and the battery life and fast charging effect are improved.
Patent Information
- Application Number
- CN202080066275.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-09-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-09-22
AI Technical Summary
Due to irregular shapes of the negative electrode active material in the existing secondary batteries, the contact area between the adhesive and the material is reduced, resulting in low adhesion of the negative electrode, affecting the life characteristics of the battery.
A carbon negative electrode active material containing cores is used, wherein the core is composed of a plurality of sheet-shaped artificial graphite primary particles, and the surface is covered with natural graphite and amorphous carbon material, with a natural graphite content of 10% to 30%, and the spherical degree of carbon negative electrode active material is 0.78 to 0.83. This structure improves the adhesion of the negative electrode.
By increasing the adhesion of the negative electrode, the battery life is extended, the battery's fast charging effect is enhanced, and the high-temperature storage performance is improved.
Smart Images

Figure GDA0005191868640000131
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to Korean Patent Application No. 10-2019-0120025, filed on September 27, 2019, the disclosure of which is hereby incorporated by reference in its entirety. Technical Field
[0004] The present invention relates to a negative electrode and a secondary battery containing the same, wherein the negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a carbon-based negative electrode active material, the carbon-based negative electrode active material comprises: a core, the core containing a plurality of flaky artificial graphite primary particles; natural graphite arranged on the core; and an amorphous carbon-based material, wherein the content of the natural graphite in the carbon-based negative electrode active material is 10 wt % to 30 wt %, and the carbon-based negative electrode active material has a sphericity of 0.78 to 0.83. Background Art
[0005] Due to the rapid increase in the use of fossil fuels, the demand for the use of alternative or clean energy has increased, and as part of this trend, power generation and power storage using electrochemical reactions are the most active research areas.
[0006] At present, a typical example of an electrochemical device using electrochemical energy can be a secondary battery, and there is a trend that its use field is getting larger and larger. In recent years, with the increase in technological development and demand for portable devices such as portable computers, mobile phones and cameras, the demand for secondary batteries as energy sources has increased significantly. Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode may include a negative electrode active material in which lithium ions derived from the positive electrode are embedded and deintercalated. As a negative electrode active material, a carbonaceous material such as graphite can be used.
[0007] Artificial graphite may be used as the carbonaceous material, and artificial graphite may also be used in the form of secondary particles. When artificial graphite is used as a negative electrode active material, there is an advantage that the rate characteristics of a secondary battery can be improved.
[0008] However, because the artificial graphite in the form of secondary particles generally has an irregular shape, the contact area between the binder in the negative electrode and the artificial graphite is reduced, so that there is a limitation that the adhesion of the negative electrode (adhesion between the negative electrode active materials and / or adhesion between the negative electrode active materials and the current collector) is low. There is a method of forming a functional group containing oxygen, etc. on the surface of the carbonaceous material, but this reduces the capacity of the carbonaceous material.
[0009] Therefore, the present invention provides a novel negative electrode with improved negative electrode adhesion. Summary of the invention
[0010] Technical issues
[0011] One aspect of the present invention provides a negative electrode and a secondary battery including the same, which can improve negative electrode adhesion and battery life characteristics.
[0012] Technical Solution
[0013] According to one aspect of the present invention, a negative electrode is provided, which comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a carbon-based negative electrode active material, the carbon-based negative electrode active material comprises: a core, the core containing a plurality of flaky artificial graphite primary particles; natural graphite disposed on the core; and an amorphous carbon-based material, wherein the content of the natural graphite in the carbon-based negative electrode active material is 10 wt % to 30 wt %, and the carbon-based negative electrode active material has a sphericity of 0.78 to 0.83.
[0014] According to another aspect of the present invention, a secondary battery including the negative electrode is provided.
[0015] Beneficial Effects
[0016] According to the present invention, because the carbon-based negative electrode active material contained in the negative electrode contains a core containing an appropriate amount of artificial graphite, the life and rapid charging effect of the battery can be improved. In addition, because an appropriate amount of natural graphite is contained in the surface of the carbon-based negative electrode active material, the carbon-based negative electrode active material has a uniform shape and the surface of the carbon-based negative electrode active material becomes smooth, thereby increasing the contact area between the negative electrode binder and the carbon-based negative electrode active material. Therefore, the adhesion of the negative electrode can be improved and the life characteristics of the battery can be improved. DETAILED DESCRIPTION
[0017] Hereinafter, the present invention will be described in more detail to enable a clearer understanding of the present invention.
[0018] The terms or words used in this specification and claims should not be restrictively interpreted as ordinary meanings or dictionary-based meanings, but should be interpreted as meanings and concepts consistent with the technical essence of the present invention on the basis that the inventor can appropriately define the concepts of the terms to interpret the principles of the present invention in the best manner.
[0019] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting of the present invention. Terms in the singular may include plural forms unless the context clearly indicates otherwise.
[0020] It should be understood that when used in this specification, the terms "include", "comprises" or "has" are to clarify the existence of the stated features, numbers, steps, elements or their combinations, but do not exclude the existence or addition of one or more other features, numbers, steps, elements or their combinations.
[0021] In this manual, the expression "D 50 " can be defined as the particle size at which the cumulative volume in the particle size distribution curve (particle size distribution curve) is 50%. For example, D 50 This can be measured using laser diffraction, which is typically capable of measuring particle sizes from submicron to several millimeters and can achieve highly reproducible and high-resolution results.
[0022] In the present specification, the sphericity and the aspect ratio can be measured by a particle size analyzer (Morphologi4, Malvern).
[0023] <Negative electrode>
[0024] According to one embodiment of the present invention, the negative electrode includes a negative electrode active material layer, wherein the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a carbon-based negative electrode active material, the carbon-based negative electrode active material includes: a core, the core containing a plurality of flaky artificial graphite primary particles; natural graphite disposed on the core; and an amorphous carbon-based material, the content of the natural graphite in the carbon-based negative electrode active material is 10 wt % to 30 wt %, and the carbon-based negative electrode active material has a sphericity of 0.78 to 0.83.
[0025] The negative electrode may include a negative electrode active material layer, specifically, may include a current collector and a negative electrode active material layer.
[0026] There is no particular limitation on the current collector as long as it has conductivity without causing adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon; aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. Specifically, as the current collector, transition metals such as copper and nickel that adsorb carbon well can be used. The thickness of the current collector can be 6 μm to 20 μm, but the thickness of the current collector is not limited thereto.
[0027] The negative electrode active material layer may be disposed on a current collector. The negative electrode active material layer may be disposed on at least one surface of the current collector, and specifically disposed on one surface or both surfaces thereof. Different from this, the negative electrode active material layer itself may exist as a negative electrode without a current collector.
[0028] The negative electrode active material layer may include a negative electrode active material. The negative electrode active material may include a carbon-based negative electrode active material.
[0029] The carbon-based negative electrode active material may include a core, natural graphite, and an amorphous carbon-based material.
[0030] The core may include a plurality of flaky artificial graphite primary particles. Specifically, the core may be in the form of secondary particles in which a plurality of flaky artificial graphite primary particles are combined. The secondary particles may be in the form of an assembly formed by artificially combining a plurality of flaky artificial graphite primary particles.
[0031] The average particle size of artificial graphite primary particles (D 50 ) can be 3 μm to 15 μm, specifically 7 μm to 12 μm, and more specifically 10 μm to 12 μm. When the above range is met, graphitization is easy to perform, the capacity is excellent due to the appropriate specific surface area, and the rapid charging performance of the battery is excellent due to the appropriate orientation characteristics.
[0032] The aspect ratio of the primary particles of the artificial graphite may be 0.5 to 1, specifically 0.6 to 0.7. When the above range is met, the shape of the carbon-based negative electrode active material is well maintained, thereby improving the characteristics of the battery.
[0033] The core may further include an amorphous carbon-based material. The amorphous carbon-based material may be used to bind the artificial graphite primary particles in the core.
[0034] The average particle size of the core (D 50 ) may be 10 μm to 25 μm, specifically 11 μm to 22 μm. When the above range is satisfied, the negative electrode active material is easily dispersed in the negative electrode slurry, and the output characteristics of the battery may be improved.
[0035] Natural graphite may be disposed on the core. Natural graphite may improve the adhesion of the negative electrode by smoothing the surface of the carbon-based negative electrode active material.
[0036] The natural graphite may have a curved form while surrounding the surface of the core. Thus, the surface of the carbon-based negative electrode active material may become smooth, and the shape of the carbon-based negative electrode active material may become more uniform.
[0037] The content of natural graphite in the carbon-based negative electrode active material can be 10% to 30% by weight, specifically 20% to 30% by weight and more specifically 25% to 30% by weight. When the content is less than 10% by weight, the increase in negative electrode adhesion is small, so it is difficult to expect the life characteristics of the battery to be improved. On the contrary, when the content is greater than 30% by weight, the specific surface area of the carbon-based negative electrode active material is excessively increased, thereby increasing the side reactions of the electrolyte and increasing the volume expansion of the carbon-based negative electrode active material. Therefore, the high temperature storage performance and life characteristics of the battery will deteriorate.
[0038] The weight ratio of the core to the natural graphite can be in the range of 64.29:35.71 to 89.47:10.53, specifically 64.29:35.71 to 88.10:11.90, more specifically 64.29:35.71 to 78:22. When the above range is met, the negative electrode adhesion is good, the side reaction of the electrolyte is suppressed, and the volume expansion degree of the carbon-based negative electrode active material can be suppressed, thereby improving the high temperature storage performance and life characteristics of the battery.
[0039] Amorphous carbon-based materials can be used to bond the core and natural graphite. The amorphous carbon-based materials can be disposed between the core and natural graphite, on the surface of the core, on the surface of natural graphite, etc. Furthermore, they can be disposed in the core as described above.
[0040] The content of the amorphous carbon-based material in the carbon-based material may be 5 wt % to 16 wt %, specifically 9 wt % to 14 wt %. When the above range is met, a secondary particle form having a suitable particle size may be obtained, thereby improving initial efficiency.
[0041] The sphericity of the carbon-based negative electrode active material can be 0.78 to 0.83, specifically 0.783 to 0.827, and more specifically 0.795 to 0.825. In the case where the sphericity is less than 0.78, because the shapes between the carbon-based negative electrode active materials are too uneven and the surface of the carbon-based negative electrode active material has an overly curved form, the contact area between the negative electrode binder and the carbon-based negative electrode active material is reduced. As a result, the negative electrode adhesion deteriorates and the life characteristics of the battery deteriorate. On the contrary, in the case where the sphericity is greater than 0.83, the side reactions of the electrolyte increase, and the volume expansion of the carbon-based negative electrode active material greatly increases, thereby deteriorating the high temperature storage performance and life characteristics of the battery.
[0042] In the present invention, the sphericity of the carbon-based negative electrode active material is adjusted to a range of 0.78 to 0.83, whereby the shapes of the carbon-based negative electrode active materials can become similar to each other, and the surface of the carbon-based negative electrode active material can become smoother, so that the contact area between the negative electrode binder and the carbon-based negative electrode active material can be increased. Therefore, the negative electrode adhesion can be improved and the life characteristics of the battery can be improved.
[0043] The average particle size of carbon-based negative electrode active materials (D 50 ) may be 11 μm to 26 μm, specifically 12 μm to 23 μm. When the above range is met, the carbon-based negative electrode active material can be well dispersed in the negative electrode slurry, thereby improving the output characteristics of the battery.
[0044] Although not limited thereto, the carbon-based negative electrode active material may be prepared by the following method.
[0045] Specifically, the method for manufacturing a carbon-based negative electrode active material may include a first method, which includes: a) mixing and heating a core, flaky natural graphite and a carbonaceous precursor to form composite particles, wherein a plurality of needle cokes are combined with each other in the core; b) spheroidizing the composite particles; and c) graphitizing the spheroidized composite particles.
[0046] By heating, a plurality of needle cokes are transformed into flake-shaped artificial graphite primary particles, and a carbonaceous precursor such as pitch is transformed into an amorphous carbon-based material.
[0047] The spheronization can be performed by a typical spheronization equipment.
[0048] The graphitization can be performed by an Acheson high temperature electric furnace.
[0049] The negative electrode active material layer may further include a negative electrode binder, which is used to connect the negative electrode active material, maintain the shape of the negative electrode, and increase the adhesion of the negative electrode.
[0050] The negative electrode binder may include at least one selected from the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid; and materials whose hydrogen is replaced by Li, Na, Ca, etc., or may include various copolymers thereof.
[0051] The content of the negative electrode binder in the negative electrode active material layer may be 1.2 wt % to 5 wt %, specifically 1.5 wt % to 4 wt %. When the above range is met, it is easy to apply the negative electrode slurry, thereby the adhesion of the negative electrode is excellent. In particular, the range of 1.2 wt % to 5 wt % corresponds to a level lower than the usual negative electrode binder content. This is because the negative electrode of the present invention uses the above-mentioned carbon-based negative electrode active material, thereby obtaining sufficient negative electrode adhesion even with a low content of the negative electrode binder.
[0052] The negative electrode active material layer may further include a conductive material.
[0053] There is no particular limitation on the conductive material as long as it has conductivity without causing adverse chemical changes in the battery, and for example the following conductive materials can be used: graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.
[0054] <Secondary Battery>
[0055] A secondary battery according to another embodiment of the present invention may include a negative electrode, and the negative electrode is the same as the above-mentioned negative electrode according to the embodiment.
[0056] Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator disposed between the negative electrode and the positive electrode, and an electrolyte, wherein the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description will be omitted.
[0057] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.
[0058] In the positive electrode, there is no particular limitation on the positive electrode collector as long as it has conductivity without causing adverse chemical changes in the battery, and for example: stainless steel, aluminum, nickel, titanium, calcined carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. In addition, the positive electrode collector may generally have a thickness of 3 μm to 500 μm, and may have a surface with fine concavoconvexities to improve adhesion to the positive electrode active material. For example, the positive electrode collector may be used in various shapes such as a film, a sheet, a foil, a mesh, a porous body, a foamed body, a non-woven fabric body, and the like.
[0059] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include: a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2Nickel (Ni)-site type lithium nickel oxide represented by O2 (wherein M is at least one selected from the following: cobalt (Co), manganese (Mn), aluminum (Al), copper (Cu), iron (Fe), magnesium (Mg), boron (B) and gallium (Ga), and c2 satisfies 0.01≤c2≤0.3); represented by the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the following: Co, Ni, Fe, chromium (Cr), zinc (Zn) and tantalum (Ta), and c3 satisfies 0.01≤c3≤0.1); and LiMn2O4 in which a portion of Li is replaced by alkaline earth metal ions, but the positive electrode active material is not limited thereto. The positive electrode may be Li metal.
[0060] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder as well as the positive electrode active material described above.
[0061] In this case, the positive electrode conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation as long as it has electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of the conductive material may be: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metals such as powder or fiber of copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used.
[0062] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples of the binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used.
[0063] The separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used in secondary batteries, in particular, a separator having high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration can be used. Specifically, porous polymer films, such as porous polymer films prepared from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, can be used; or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multilayer structure can be selectively used.
[0064] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used in preparing a lithium secondary battery, but the present invention is not limited thereto.
[0065] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0066] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.
[0067] Especially, in carbonate organic solvent, because ethylene carbonate and propylene carbonate as cyclic carbonate owing to the high dielectric constant as high viscosity organic solvent lithium salt is well dissociated, so can preferably use cyclic carbonate.Because when above-mentioned cyclic carbonate and low viscosity, the straight chain carbonate of low dielectric constant such as dimethyl carbonate and diethyl carbonate are mixed in appropriate proportion and used, can prepare the electrolyte with high conductivity, so can more preferably use cyclic carbonate.
[0068] A lithium salt can be used as the metal salt, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte, wherein as an anion of the lithium salt, for example, at least one selected from the following can be used: - , Cl - ,I- 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0069] In order to improve the working life characteristics of the battery, prevent the reduction of the battery capacity, and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, at least one additive may be included in the electrolyte, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0070] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. Since the battery module and the battery pack include secondary batteries having high capacity, high rate characteristics and high cycle characteristics, the battery module and the battery pack can be used as power sources for medium and large devices selected from the following: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0071] Hereinafter, preferred examples will be provided to better understand the present invention. It will be apparent to those skilled in the art that these examples are provided only to illustrate the present invention, and various variants and changes are possible within the scope and technical spirit of the present invention. Such variants and changes fall within the scope of the claims appended hereto.
[0072] Examples and Comparative Examples
[0073] Example 1: Preparation of negative electrode
[0074] As the negative electrode active material, a carbon-based negative electrode active material is used, which includes: a core containing multiple artificial graphite primary particles; natural graphite arranged on the core; and an amorphous carbon-based material, which combines multiple artificial graphite primary particles and natural graphite.
[0075] The negative electrode active material, binder (CMC and SBR), carbon black as a conductive material were mixed with pure water as a solvent at a weight ratio of 95.6:3.4:1.0, and stirred to form a negative electrode slurry. The negative electrode slurry was coated on a copper foil (current collector), and then the negative electrode current collector coated with the negative electrode slurry was roll-pressed at a porosity of 28%, and vacuum-dried at 130°C for 10 hours to prepare a negative electrode (1.4875 cm 2 The loading capacity of the prepared negative electrode is 3.61 mAh / cm 2 .
[0076] Examples 2 to 4 and Comparative Examples 1 and 2: Preparation of Negative Electrode
[0077] The negative electrodes of the examples and comparative examples were manufactured using different negative electrode active materials as shown in Table 1.
[0078] [Table 1]
[0079]
[0080] Average diameter (D 50 ), aspect ratio and sphericity were measured by a particle size analyzer (Morphologi4, Malvern).
[0081] Experimental Example 1: Evaluation of negative electrode adhesion
[0082] The negative electrode adhesion of the negative electrodes of the examples and comparative examples was evaluated.
[0083] The negative electrode was punched into 20 mm × 150 mm and fixed to the center of a 25 mm × 75 mm slide glass with tape, and then the 90° peel strength was measured while the current collector was peeled using UTM. Five or more peel strengths were measured and the average value was used for evaluation.
[0084] Experimental Example 2: Evaluation of battery life characteristics
[0085] A battery was manufactured as follows, and the battery life characteristics were evaluated.
[0086] Will Li[Ni 0.6 Mn 0.2 Co 0.2 ]O2 was used as a positive electrode active material. The positive electrode active material, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed in an N-methyl-2-pyrrolidone solvent at a weight ratio of 94:4:2 to prepare a positive electrode slurry.
[0087] The prepared positive electrode slurry was coated on a 15 μm thick aluminum metal film as a positive electrode collector and dried. In this case, the temperature of the circulating air was 110° C. Subsequently, the coated and dried positive electrode collector was rolled and dried in a vacuum oven at 130° C. for 2 hours to prepare a positive electrode including a positive electrode active material layer.
[0088] The negative electrode, the prepared positive electrode, and the porous polypropylene separator were assembled using a stacking method, and the electrolyte was injected into the assembled battery to prepare a lithium secondary battery.
[0089] The battery was charged at a current of 0.2C until SOC 30% for activation, and then charged in a constant current / constant voltage (CC / CV) mode (4.2V, 0.05C cutoff), and discharged in a CC mode (0.2C current, 3.0V cutoff), and the charging and discharging were performed 3 times. Thereafter, the capacity retention rate of 300 cycles was compared by life evaluation at 45°C, 1C / 1C.
[0090] [Table 2]
[0091] Negative electrode adhesion (gf / 10mm) Capacity retention rate (%) Example 1 17 85.5 Example 2 20 87.1 Example 3 23 88.7 Example 4 30 90.0 Comparative Example 1 10 78.7 Comparative Example 2 35 79.9
Claims
1. A negative electrode, comprising a negative electrode active material layer, The negative electrode active material layer comprises a negative electrode active material, The negative electrode active material comprises a carbon-based negative electrode active material, The carbon-based negative electrode active material comprises: a core containing a plurality of flaky artificial graphite primary particles; natural graphite disposed on the core; and an amorphous carbon-based material. The content of the natural graphite in the carbon-based negative electrode active material is 10 wt % to 30 wt %, and The carbon-based negative electrode active material has a sphericity of 0.78 to 0.83, wherein the natural graphite has a curved form while surrounding the surface of the core.
2. The negative electrode according to claim 1, wherein the artificial graphite primary particles have an average particle size D of 3 μm to 15 μm. 50 .
3. The negative electrode according to claim 1, wherein the artificial graphite primary particles have an average particle size D of 10 μm to 12 μm. 50 . 4 . The negative electrode according to claim 1 , wherein the artificial graphite primary particles have an aspect ratio of 0.5 to 1.
5. The negative electrode according to claim 1, wherein the core has an average particle size D of 10 μm to 25 μm. 50 . 6 . The negative electrode according to claim 1 , wherein a weight ratio of the core to the natural graphite is in a range of 64.29:35.71 to 89.47:10.
53.
7. The negative electrode according to claim 1, wherein the carbon-based negative electrode active material has an average particle size D of 11 μm to 26 μm. 50 . The negative electrode according to claim 1 , further comprising a negative electrode binder. 9 . The negative electrode according to claim 8 , wherein the negative electrode binder is contained in the negative electrode active material layer in an amount of 1.2 wt % to 5 wt %. 10 . A secondary battery comprising the negative electrode according to claim 1 .
Citation Information
Patent Citations
Wireless car key case and its method for storing parking zone with switch pressing part
KR1020190120025A
Anode active material and anode including same
CN107534138A
Anode for lithium secondary battery and lithium secondary battery comprising the same
CN108878773A
Anode, secondary battery comprising same, battery module, and battery pack
CN108886137A
Lithium secondary batteries and nonaqueous electrolyte for use in the same
US20100015514A1